The Error of Past Tense Expression in Jackie Chan’s Utterances on Jackie Chan in Conversation - Ricky Ricky; Ambalegin Ambalegin (LPPM Universitas Putera Batam, 2023)
This research aims to identify the incorrect use of past tense by Jackie Chan in giving his first public talk at the Sydney Opera House. In this qualitative research, the researchers applied an observational method that focuses on grammatical errors. In this study, the researchers use a non-participatory technique that focuses on grammatical errors. Meanwhile, in analyzing the data, the method was identification, and the technique was competence in comparing. The researchers took the source from a conversation from Jacky Chan in an interview in Australia on Youtube. Based on the, the errors uttered by the speaker are errors in using the past simple, errors in using clauses and verbs, specifying a particular point or period in the past, and the verb